(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Different light intensity and different media types were used to test their effects on algal growth and biochemical composition of cell content to optimize the growth of algal biomass production. Analysis of the results includes growth calculation of Chlorella vulgaris obtained from 6 d observations for 12 h a day (06:00 am to 06:00 pm) with 3 h breaks in between observation. Laboratory analysis was done at the end of day 5th to determine the content of N, and P. Density of C. vulgaris were influenced by both light intensity and media. Differences media type and light intensity as separated parameters and their interactions significantly (p < 0.05) affected on the growth and nitrogen and phosphor content of C. vulgaris. The highest density of 2 310 × 104 cells · mL–1 was on day 4 with walne media resulting in specific growth rate (µ) of 0.43 per day with a light intensity of 5 000 lux, and the lowest density of 725 × 104 cells · mL–1 was in day 4 with the NPK media and specific growth rate (µ) 0.25 per day with a light intensity of 4 000 lux. The highest nitrogen and phosphorus content (16.12 mg and 28.19 mg) was obtained from walne medium with a light intensity of 5000 lux, and the lowest (3.43 mg and 2.17 mg) was obtained from NPK with a light intensity of 4 000 lux.